TO STUDY THE USE OF MODERN DIAGNOSIS TECHNIQUE IN SHWAS VYADHI - Mandpe U Ankita; Lanjewar R. Swati; Kalyanshetti V Trupti; Kodwani G.H.; Aurangabadkar A. Meera (International Journal of Applied Ayurved Research, 2017)
Shwas is the disease manifest in Pranvah Strotas, in which derangement of Pranvayu occur. In Ayurveda Shwas may appear as Swatantra Vyadhi or may appear as a symptom of other disease, termed as Partantra Vyadhi. PranVayu is directed in upward movement resulting in sound like Bhastrika is called as Shwas. On the basis of clinical feature Shwas Vyadhi classified in five type viz. Urdhva, Maha, Chinna, Tamak & KShudra. In this modern era, there are various diagnostic tools are available so diagnosis of various diseases made easy. As Swash is the disease of Pranvahastrotas and this Strotas termed as Darun by Acharyas, hence it is necessary to diagnosed Shwas Vyadhi and give treatment.